Time trend of neurocysticercosis in children with seizures in a tertiary hospital of western Nepal. - Kalipatnam Seshagiri Rao; Sudhir Adhikari; Eva Gauchan; Brijesh Sathian; Ganesh B K; Sahisnuta Basnet; Prabhat Kumar Tiwari; Namraj Bahadur; Rajnish Mishra (Public Library of Science (PLoS), 2017)
INTRODUCTION:Neurocysticercosis is a common cause of seizure disorders in children of Western Nepal. The clinical presentation is variable. The incidence varies depending on the food habits and ethnicity of the population. The present study was undertaken with the objective of studying the mode of presentation, radiological findings and to determine the recent trend of the disease in children of Western Nepal. METHODS:Records from the Department of Pediatrics, Manipal Teaching Hospital, Pokhara, Nepal of children aged 0-17 years admitted from 2003 to 2015 and with the discharge diagnosis of seizure and neurocysticercosis (NCC) were reviewed. The diagnosis was primarily based on clinical features, neurological involvement and CT and MRI studies. Seizures due to other CNS pathologies were excluded. Patients with NCC were treated with Albendazole15mg/kg/day for 28 days with supportive treatments for seizures and raised intracranial pressure. Patients were followed up for one year after the completion of the treatment. RESULTS:There were 1355 cases of seizure disorders, out of which 229 (16.90%) were NCC. There were 99 (43.23%) in the age group 6-10 years followed by 91 (41.09%) in the age group of 11-15 years. Seizures were the most common presenting symptom in 88.65%, followed by raised ICP in 9.61%. Neuropsychiatric changes were noted in 38 cases (16.59%). CT scan findings revealed single lesion in 78.16% and multiple lesions in 21.83%. Poisson regression analysis showed statistically significant decline of year-wise incidence of NCC cases (p<0.05) from 2003 to 2015. CONCLUSION:The decline in the incidence of NCC in recent years is most probably attributed to improved hygiene with the construction of household toilets to avoid open defecation and biannual deworming with Albendazole as a part of School Health and Nutrition Project.